Provenance determination of archaeological marbles as an example for the use of geoscientific methods - Cramer, Thomas (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2009)
The geoscientific analysis with the purpose of provenance determination of marbles used in the greek and roman antiquity helps to resolve archaeological questions. Here we show methods used for the characterization of marble findings from Asia minor, which are now exposed in the Pergamon Museum in Berlin. 232 samples of 39 ancient objects and 362 samples of 20 marble deposits gave a broad database. The frequent superposition of characteristics of the deposits requires a multivariate approach. In spite of all modern analytical techniques, the petrographic characteristics continue being indispensable. Dolomites measured by means of XRD showed a good correlation with Mg. Mg, Fe, Sr and Mn were determined by means of ICP-OES, and the REE, by means of ICP-MS. Stable isotopes (äCPDB and äOPDB) gave important indications. The multivariate statistic (factorial, to cluster, discriminatory analysis) confirmed the geologic relevance and the utility of the used characteristics. The gas chromatography of volatile phases, the cathodoluminiscence and EPR yielded additional results. Here we use the marbles of the Pergamon Altar, which were proved to come from Marmara Island and not from the local deposit of Akkaya, to show how all the ancient objects could be assigned to marble quarries.